Participation of the Limbic System in the Treatment of Parkinson's Disease with Depression - Chen, Feng; Jia, Ni; Ye, Yangmei; Li, Niannian; He, Jianing (Journal of Contemporary Medical Practice, 2024)
Parkinson's disease (PD) is a common chronic neurological disease in the elderly, starting from motor disorders such as static tremor and bradykinesia. However, with the evolution of the disease, the incidence of non-motor symptoms increases year by year, among which it is mainly depression. With the emergence of depressive symptoms, seriously affected the quality of life of PD patients, but also induce aggravating movement disorders and a series of related symptoms, for the pathogenesis of PD patients with depression is not clear, most people think it with the brain of dopamine, serotonergic neurons change, this paper will start on the brain structure, from the ancient limbic system, its definition and structure, and the mechanism between PD patients with depression, through consulting relevant literature, expand the following review.